THE ESTABLISHMENT OF A REGIONAL BUSINESS ENTITY OF SALT (BUMD) AS AN EFFORT TO IMPROVE THE WELFARE OF SALT FARMERS IN INDRAMAYU REGENCY - Riva Rachmi Kusumah (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2022)
Salt farmers in Indramayu Regency are an integral part of society, and therefore become subjects where social justice must be realized. Actually, salt farmers are still far from getting a decent life, so it can be said that salt farmers do not get justice both legally and economically. In social justice there is an understanding that the injustice that has existed so far must be addressed to the lowest point, Wealth, power and status of individuals, communities, and social goods (societal goods) and the State and Government are responsible for ensuring the basic quality of life for all citizens. that will be used in achieving this goal is to use a normative legal research method (doctrinal research) which mainly analyzes primary legal materials and secondary legal materials complemented by focus group discussions (FGD) and interviews due to their nature which focuses more on the conceptualization of ideas in the form of models, so that the results expected to be applied by policy makers. The long-term goal and specific target to be achieved from this research is to conduct a study on the suitability of the current laws and regulations for the Protection and Empowerment of salt farmers with the needs of the people in Indramayu Regency. Second, an effort to solve the problem of local salt farmers, local salt producers, through legal participation in encouraging social change in the direction required by the law.